The p16/ki-67 assay is a safe, effective and rapid approach to triage women with mild cervical lesions. - Maria Magkana (Public Library of Science (PLoS), 2021)
Objective The aim of this study was to evaluate the diagnostic accuracy and efficiency of p16/ki-67 dual stain in the identification of CIN2+ lesions, in Greek women with ASCUS or LSIL cytology. Methods A total of 200 women, 20 to 60 years old, were enrolled in the study. All samples were cytologically evaluated and performed for p16/ki-67 and high-risk HPV (HR-HPV) test. All patients were referred to colposcopy for biopsy and histological evaluation. Three cervical cancer (CC) screening strategies were designed and the total direct medical costs of the procedures during our clinical trial were evaluated, from a healthcare perspective. Results HPV 16 as expected was the most common HR-HPV type followed by HPV 31 and HPV 51. The risk for CIN2+ was significantly higher in HPV 16/18 positive cases. p16/ki-67 demonstrated a high sensitivity for CIN2+ identification in both ASCUS and LSIL groups (90.4% and 95%, respectively). HR-HPV test with sensitivity 52.3% and 65.5%, as well as colposcopy with sensitivity 14.3% and 36% respectively in ASCUS and LSIL group, showed inferior results compared to p16/ki-67. The specificity of p16/ki-67 for ASCUS and LSIL was 97.2% and 95.2% respectively, inferior only to colposcopy: 100% and 100%, lacking however statistical significance. HR-HPV test instead, presented the lowest specificity: 76.4% and 71.4% respectively in comparison to the other two methods. From a healthcare perspective, the costs and benefits of the tests implementation for the annual screening and triaging, in three CC screening strategies, were also calculated and discussed. Conclusions The results of the study indicate that p16/ki-67 is a safe and rapid assay that could be used to detect CIN2+ among women with mild cervical lesions, presenting both high sensitivity and specificity and could minimize the psychological and economic burden of HPV screening.